AB0213 Is Disease Duration An Independent Predictor of Low Disease Activity/remission among Biologic-Naïve Patients with Rheumatoid Arthritis Treated with Abatacept?. (15th July 2016) - Harrold, L.R.; Litman, H.J.; Connolly, S.E.; Kelly, S.; Hua, W.; Alemao, E.; Rosenblatt, L.; Rebello, S.; Kremer, J.M.
Abstract : Background: Patients with long-standing RA may have more treatment-resistant disease than those with shorter disease duration. Objectives: To examine whether disease duration is an independent predictor of treatment response among biologic-naïve patients with RA initiating abatacept in a US national, observational cohort. Methods: Using the Corrona RA registry, we identified new initiators of abatacept between Feb 2006 and Jan 2014 who were biologic naïve with a follow-up visit at 1 year (±3 months) and assessment of disease activity (CDAI) at initiation and 1-year follow-up. The primary outcome was mean change from baseline in CDAI; the secondary outcomes were: 1) achievement of low disease activity (LDA; CDAI ≤10) among those who initiated abatacept in moderate or high disease activity, and 2) achievement of remission (CDAI ≤2.8) in those who initiated abatacept in low, moderate or high disease activity. Patients were stratified by disease duration (0–2, 3–5, 6–10, >10 years). For patients who switched agents before 1 year, the last observation before the switch was used to calculate mean change in CDAI. Switchers were imputed as non-responders for calculation of LDA and remission. Linear and logistic regression models were fit, as appropriate. Results: In total, 281 biologic-naïve patients with RA initiating abatacept met inclusion criteria (disease duration 0–2 years: n=107; 3–5 years: n=45; 6–10 years: n=50; >10 years: n=79). Baseline characteristics were similar across disease duration groups for sex (76–89% female) and disease activity (mean CDAI: 15.3–19.1). Increasing disease duration was associated with older patient age (p=0.047) and a higher number of prior conventional (c)DMARDs (p<0.001). Mean change in CDAI ranged from –10.22 to –4.63 in patients with 0–2 and >10 years disease duration (Table). In analyses adjusted for age, sex, baseline CDAI and prior number of cDMARDs (Table), increasing disease duration was significantly associated with smaller mean change in CDAI (p=0.015) and lower likelihood of achieving LDA (p=0.048); association with decreasing likelihood of remission reached borderline significance (p=0.055). Conclusions: In biologic-naïve patients initiating abatacept, change in CDAI was significantly greater for shorter versus longer disease duration (unadjusted and adjusted models). After adjusting for covariates, shorter disease duration was associated with a greater likelihood of patients achieving LDA. Disclosure of Interest: L. R. Harrold Grant/research support from: Pfizer, H. J. Litman Employee of: Corrona, S. E. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Kelly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, W. Hua Employee of: Corrona, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, L. Rosenblatt Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Rebello Employee of: Corrona, J. M. Kremer Shareholder of: Corrona, Grant/research support from: AbbVie, Bristol-Myers Squibb, Genentech, Lilly, Novartis, Pfizer, Employee of: Corrona, Speakers bureau: Genentech (non-branded talks only)